The role of green finance in reducing agricultural non-point source pollution—an empirical analysis from China - Lv, Wen; Zhang, Zheng; Zhang, Xiaran (Frontiers in Sustainable Food Systems, 2023)
Green finance is aimed at driving green development, and thus can effectively reduce pollution emissions and have a positive impact on the environment. But in agriculture, unlike developed countries, China is mainly a small-peasant economy and the green financial system is not well developed. So the emission reduction effect and mechanism of green finance on agricultural non-point source pollution (ANSP) are not clear. this paper presents an empirical analysis of the effect of green finance on ANSP abatement using provincial panel data from 2005 to 2020 in China. The empirical results show that:(1) Although green finance significantly reduces ANSP, the effect is not consistent in different areas. The effect of green finance reducing ANSP is stronger only in areas with strong comprehensive agricultural strength, high economic development level, and mainly plantation areas. (2) From the mechanism level analysis, green finance can significantly reduce ANSP by promoting the scale of agriculture and improving the level of green technology. (3) The threshold effect test shows that the mitigation effect of green finance on ANSP has non-linear characteristics, and there is a double threshold effect of green finance, and the mitigation effect will be enhanced as the development level of green finance increases. Based on this, this paper gives some useful policy recommendations. This paper enriches the previous studies and provides a reference for the government to formulate green finance policies, as well as providing a feasible path to reduce ANSP; it also serves as a reference for other developing countries to reduce ANSP.